High Submandibular Anteroparotid Approach for Open Reduction and Internal Fixation of Condylar Fracture - Kamichika Hayashi; Takeshi Onda; Hirona Honda; Mitsuru Takata; Hiroyuki Matsuda; Hidetoshi Tamura; Masayuki Takano (Hindawi Limited, 2021)
Aim. There are several techniques for the treatment of mandibular condylar fractures. This is the first report of the high submandibular anteroparotid approach for open reduction and internal fixation of condylar fracture. Materials and Methods. A 41-year-old woman fell indoors and injured her face. She was referred to our department for detailed examination and treatment of a suspected mandibular fracture. X-ray and computed tomography showed a right mandibular condylar base fracture and lateral dislocation of the fracture fragment. Open reduction and internal fixation procedures were performed for a right mandibular condylar fracture under general anesthesia. The mandibular ramus was reached by approaching from the inferior margin of the mandible, delaminating the masseter fascia posteriorly, and bypassing the anterior margin of the parotid gland. Once the fractured bone was reached, reduction and fixation were performed. Results. We have achieved good results by the high submandibular anteroparotid approach, which is minimally invasive and simple, to reduce and fix condylar fractures. With this approach, no facial artery or retromandibular vein was encountered, and the mental stress for the surgeon was minimal. Postoperative wound infection, parotid gland complications such as parotitis and salivary fistula, facial nerve dysfunction such as facial paralysis, and esthetic disorders such as scarring were not observed. Conclusions. Although it is necessary to examine more cases in the future, the high submandibular anteroparotid approach may be useful as a new approach for open reduction and internal fixation of condylar fractures.